Effects of Chromium on Glucose Tolerance in Infants Receiving Parenteral Nutrition Therapy. (14th December 2017) - Capone, Kristin; Sriram, Sudhir; Patton, Tiffany; Weinstein, Dana; Newton, Ellen; Wroblewski, Kristen; Sentongo, Timothy
Abstract: Objectives : Early hyperglycemia is prevalent in preterm infants receiving parenteral nutrition (PN) therapy. Chromium improves glucose tolerance by potentiating the action of insulin. Therefore, we hypothesized that supplementing PN with chromium would improve glucose tolerance and PN calorie delivery in infants during the first week of life. Methods : We collected data on neonates receiving PN initiated at birth with chromium (0.2 mcg/kg/d) started either on days 5–7 (group A) vs day 1 (group B) on PN and compared glucose tolerance and PN calorie administration over the first week of life. Results : For similar mean serum glucose concentrations between group A (n = 348) and B (n = 358) (107 ± 48 vs 111 ± 52 mg/dL, P = .3), infants in group B tolerated higher glucose infusion rates and received more PN calories during the first week of life: 8.4 ± 2 vs 8 ± 2 mg/kg/min ( P < .001) and 74.8 ± 23 vs 71.5 ± 12 kcal/kg/d ( P = .017), respectively. The difference in calories delivered was more pronounced among very low birth weight (VLBW) infants compared with infants >1500 g: 76.5 ± 14 vs 72.4 ± 11 kcal/kg/d ( P = .009) and 73.8 ± 27 vs 70.3 ± 12 kcal/kg/d ( P = .079), respectively. Conclusions : PN chromium supplementation resulted in better glucose tolerance and calorie delivery during the first week of life, especially in VLBW infants. This supports chromium's essential role in enhancing glucose tolerance during PN therapy in VLBW infants at risk for early hyperglycemia.